TNBC-DX genomic test in early-stage triple-negative breast cancer treated with neoadjuvant taxane-based therapy - Martín, M (2024)
Background: Identification of biomarkers to optimize treatment strategies for early-stage triple-negative breast cancer (TNBC) is crucial. This study presents the development and validation of TNBC-DX, a novel test aimed at predicting both short- and long-term outcomes in early-stage TNBC. The objective of this study was to evaluate the association between TNBC-DX and efficacy outcomes [pathologic complete response (pCR), distant disease-free survival (DDFS) or event-free survival (EFS), and overall survival (OS)] in the validation cohorts. Methods: Information from 1259 patients with early-stage TNBC (SCAN-B, CALGB-40603, and BrighTNess) was used to establish the TNBC-DX scores. Independent validation of TNBC-DX was carried out in three studies: (i) WSG-ADAPT-TN; (ii) MMJ-CAR-2014-01; and (iii) NeoPACT, including 527 patients with stage I-III TNBC undergoing neoadjuvant chemotherapy. In WSG-ADAPT-TN, patients were randomized to receive nab-paclitaxel plus gemcitabine or carboplatin. In MMJ-CAR-2014-01, patients received carboplatin plus docetaxel. In NeoPACT, patients received carboplatin plus docetaxel and pembrolizumab. Results: TNBC-DX test was created incorporating the 10-gene Core Immune Gene module, the 4-gene tumor cell proliferation signature, tumor size, and nodal staging. In the two independent validation cohorts without pembrolizumab, the TNBC-DX pCR score was significantly associated with pCR after adjustment for clinicopathological variables and treatment regimen [odds ratio per 10-unit increment 1.34, 95% confidence interval (CI) 1.20-1.52, P < 0.001]. pCR rates for the TNBC-DX pCR-high, pCR-medium, and pCR-low categories were 56.3%, 53.6%, and 22.5% respectively (odds ratio for pCR-high versus pCR-low 3.48, 95% CI 1.72-7.15, P < 0.001). In addition, the TNBC-DX risk score was significantly associated with DDFS [hazard ratio (HR) high-risk versus low-risk 0.24, 95% CI 0.15-0.41, P < 0.001] and OS (HR 0.19, 95% CI 0.11-0.35, P < 0.001). In the validation cohort with pembrolizumab, the TNBC-DX scores were significantly associated with pCR, EFS, and OS. Conclusions: TNBC-DX predicts pCR to neoadjuvant taxane–carboplatin in stage I-III TNBC and helps to forecast the patient's long-term survival in the absence of neoadjuvant anthracycline–cyclophosphamide, and independent of pembrolizumab use. © 2024 The Author(s)